Clinical evaluation of buccal mucosal lesions in hospitalized children from 3 to 12 years-old - Silvana Amado Libério; Érica Martins Valois; Maria Carmen Fontoura Nogueira da Cruz; Fernanda Ferreira Lopes (Faculdade São Leopoldo Mandic, 2008)
Objective: To determine the presence of oral mucosa alterations in children from 3 to 12 year of age, hospitalized in the period from January to May 2004. Methods: A clinical evaluation was made of the oral mucosa alterations in 165 hospitalized children from 3 to 12 of age, in the period from January to May 2004, of both genders, interned in the three wings of the mother and child ospital "Hospital Universitário Materno Infantil" of the Federal University of Maranhão.Results: The most frequent alterations were encrusted tongue (61.82%), pseudomembranous candidiasis (5.45%) and recurrent herpeticinfection (3.64%), no difference being found with regard to their presence in the age groups (3 to 6 years of age and 7 to 12 years ofage), however, boys were more affected (85.90%) than girls (71.26%).Conclusion: Of the 165 children examined, 78.18% exhibited alterations and in certain cases, more than one alteration was observed at the time of the exam.